World Bank East Asia and Pacific Economic Update, April 2018 : Enhancing Potential - World Bank (Washington, DC: World Bank, 2018)
Developing EAP grew slightly faster than anticipated in 2017. The growth of regional GDP excluding China is forecast to remain stable in 2018, while China's GDP growth is expected to moderate as the economy keeps rebalancing. Major downside risks include volatility associated with faster than expected monetary policy tightening in advanced economies and a rising threat of trade restrictions. Developing EAP countries would need to get ready to respond to increasing interest rates and find ways to raise potential growth in the medium run. Specifically, amid the rising risk of protectionism and changes in the global manufacturing landscape, countries should continue to enhance trade facilitation and integration, increase the effectiveness of schools and education systems, and upgrade capabilities to ensure that workers and managers have necessary skills. To provide economic security to the population, policies should focus on strengthening social assistance and insurance programs, and increasing resilience to systemic shocks.